Investigation of the Use of the Magnetic Field Method in the Obtaining of Superactive Additives - U. B. Qodirov; A. A. Khakimov (International Journal on Orange Technologies, 2022)
Among the unique features of microwave heating, it is possible to name the heating of samples in the entire volume of the substance, and accordingly, it was found that it is possible to heat it uniformly, at high speed, at low inertia, and to selectively heat individual components of the mixture of substances. In addition, the use of microwave processing makes it possible to obtain well-crystallized powders from low-defect, oxide materials. Microwave processing of inorganic mixtures is one of the promising ways to increase the speed of solid-phase processes. Due to the special properties of microwave heating, the use of electromagnetic energy opens wide opportunities for the synthesis of powders of inorganic compounds with controlled properties.